Pengaruh Latihan Kekuatan Otot Lengan Terhadap Kemampuan Servis Bawah Bola Voli Pada Ekstrakurikuler Di SMPN 3 Kota Bengkulu - Anjeli Lastavia; Megi Personi; Mariska Febrianti (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of arm muscle strength training on volleyball underhand serve ability in extracurricular activities for students at SMPN 3 Bengkulu City. A total sampling method was used to determine the number of respondents, resulting in 13 volleyball students from SMPN 3 Bengkulu City This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design that includes a pretest (test before treatment) and a posttest (test after treatment) within one group. Data collection used test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of arm muscle strength training on volleyball underhand serve ability in extracurricular activities for students at SMPN 3 Bengkulu City, with a calculated t-value of 9.890 and a t-table value of 1.782, with a significance level of α = 0.05 and dk = 13.